Some local fractional Maclaurin type inequalities for generalized convex functions and their applications. (September 2022) - Meftah, B.; Souahi, A.; Merad, M.
Abstract: In this paper, we establish a new local fractional integral identity involving three point by the use of Peano kernel approach. Using this identity we derive some new local fractional integrals inequalities of Maclaurin-type for functions whose local fractional derivatives are generalized convex functions. In order to show the effectiveness of the obtained results, we apply them in numerical integration and to special means.